Chemotactic responses of fibroblasts to tropoelastin and elastin-derived peptides. - Senior, R M (1982)
Fibroblasts are known to have chemotactic responses to two components of the extracellular matrix, collagen and fibronectin. To extend these observations to other extracellular connective tissue macromolecules and their proteolytic fragments, fibroblasts from adult human skin and from late-gestation (270 d), fetal bovine ligaments were studied for chemotactic responsiveness to tropoelastin and elastin-derived peptides. Bovine ligament tropoelastin and elastin-derived peptides, generated from either human aortic elastin with human neutrophil elastase or from bovine ligament elastin with pancreatic elastase, elicited chemotactic responses that were maximal at 0.2 micrograms/ml (3 X 10(-9) M) and 0.5-2.0 micrograms protein/ml, respectively. Fractionation of the elastin-derived peptides by gel filtration (Bio-Gel P-10) indicated that comparable levels of chemotactic activity were present in all fractions, and amino acid analysis of the fractions showed no relationship between chemotactic activity and desmosine concentration. Taken in conjunction with the observations on tropoelastin, it appears that fibroblast chemotaxis to elastin components does not involve the cross-links of elastin. These results demonstrate that the influences of the connective tissue matrix upon fibroblast migration might include elastin precursors and fragments of elastin.